Role of Microtubules in Fusion of Post-Golgi Vesicles to the Plasma Membrane - Schmoranzer, Jan (The American Society for Cell Biology, 2003)
Biosynthetic cargo is transported away from the Golgi in vesicles via microtubules. In the cell periphery the vesicles are believed to engage actin and then dock to fusion sites at the plasma membrane. Using dual-color total internal reflection fluorescence microscopy, we observed that microtubules extended within 100 nm of the plasma membrane and post-Golgi vesicles remained on microtubules up to the plasma membrane, even as fusion to the plasma membrane initiated. Disruption of microtubules eliminated the tubular shapes of the vesicles and altered the fusion events: vesicles required multiple fusions to deliver all of their membrane cargo to the plasma membrane. In contrast, the effects of disrupting actin on fusion behavior were subtle. We conclude that microtubules, rather than actin filaments, are the cytoskeletal elements on which post-Golgi vesicles are transported until they fuse to the plasma membrane.